Simplified Kinetic Model of Heart Pressure for Human Dynamical Blood Flow - Saktioto Saktioto; Defrianto Defrianto; Andika Thoibah; Yan Soerbakti; Romi Fadli Syahputra; Syamsudhuha Syamsudhuha; Dedi Irawan; Haryana Hairi; Okfalisa Okfalisa; Rina Amelia (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
The blood flow that carries various particles results in disturbed physical flow in the heart organ caused by speed, density, and pressure. This phenomenon is complicated resulting in a wide variety of medical problems. This research provides a mathematical technique and numerical experiment for a straightforward solution to cardiac blood flow to arteries. Finite element analysis (FEA) is used to study and construct mathematical models for human blood flow through arterial branches. Furthermore, FEA is used to simulate the steady two-dimensional flow of viscous fluids across various geometries. The results showed that the blood flow in the carotid artery branching is simulated after the velocity profiles obtained are plotted against the experimental design. The computational method's validity is evaluated by comparing the numerical experiment with the analytical results of various functions.